1999
DOI: 10.1093/bja/82.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastogram reveals hypercoagulability after administration of gelatin solution

Abstract: We have compared the effects of gelatin, low molecular weight hydroxyethyl starch (HES) or albumin on tests of haemostasis and on the thrombelastogram in 42 ASA I patients undergoing total hip or knee replacement. Patients were allocated randomly to receive one of the three blood substitutes to obtain moderate intraoperative haemodilution. Blood loss and packed red cell infusion was the same in each group. A greater amount of gelatin was given (1.5 times the measured blood loss) because of its shorter half-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…Gelatins have also been considered to be without any major negative influence on the coagulation process [71]. However, in vitro studies have also revealed significant inhibition of platelet aggregation [72] and reduction in clot quality [73] by two gelatin preparations (polygeline and succinylated gelatin).…”
Section: Haemostatic Abnormalitiesmentioning
confidence: 99%
“…Gelatins have also been considered to be without any major negative influence on the coagulation process [71]. However, in vitro studies have also revealed significant inhibition of platelet aggregation [72] and reduction in clot quality [73] by two gelatin preparations (polygeline and succinylated gelatin).…”
Section: Haemostatic Abnormalitiesmentioning
confidence: 99%
“…67 Gelatins are generally considered to be associated with a less negative hemostatic effect compared with HES preparations. [84][85][86] However, in a study of healthy volunteers by de Jonge et al, infusion of 1000 mL of gelatin resulted in a 1.7-fold increase in bleeding time, a decrease in vWf-Ag and ristocetin cofactor, and a significant impairment of ristocetin-induced platelet aggregation. 87 in vitro studies have also demonstrated significant inhibition of platelet aggregation 88,89 and reduction in clot quality .90…”
Section: Effects Of Fluids On Coagulationmentioning
confidence: 98%
“…[12] Synthetical colloid fluids in general seem to have a more negative impact compared to crystalloid solutions, [11,13] although results from some other studies appear to contradict these findings. [14] The confusion may stem from the many separate methodologies used in the research, amount of dilution, or the choice of analysis [3].…”
Section: Colloid Induced Dilutive Coagulopathymentioning
confidence: 99%